Paediatric brainstem encephalitis associated with glial and neuronal autoantibodies. (25th February 2016) - Hacohen, Yael; Nishimoto, Yukihiro; Fukami, Yuki; Lang, Bethan; Waters, Patrick; Lim, Ming J; Yuki, Nobuhiro; Vincent, Angela
Abstract : Aim: Central nervous system (CNS) autoantibodies have been reported in a range of neuroimmune diseases, but there has not been a systematic evaluation of autoantibodies in paediatric patients with brainstem encephalitis. Method: Serum samples from 57 children (40 male, 17 female, median age 12y, range 0.6–18y) with a diagnosis of brainstem encephalitis were tested retrospectively for antibodies to GQ1b, aquaporin‐4 (AQP4), myelin oligodendrocyte glycoprotein (MOG), N ‐methyl‐D‐aspartate receptor, LGI1, CASPR2, glycine receptor (GlyR), DPPX, and the voltage gated potassium channel (VGKC)‐complex. Results: Disease localized to the brainstem was seen in 19 patients: Bickerstaff's brainstem encephalitis ( n =14) and clinically isolated syndrome ( n =5). Polyfocal presentation was seen in 38 children, with predominantly white matter disease in 18 patients and grey matter in 20 patients. CNS surface antibodies were found in 22/57 patients (two patients with double positivity): GQIb ( n =6), NMDAR ( n =7), GlyR ( n =5), MOG ( n =5), and one AQP4. Three patients were positive for VGKC‐complex antibodies. All patients were negative for antibodies to DPPX and the VGKC‐complex antigens LGI1, CASPR2, and contactin‐2. Although there were some partial differences in the presentations, the clinical features and outcomes did not relate clearly to the presence or absence of specific antibodies. Interpretation: As determined retrospectively, 39% of patients had cell surface antibodies. The results did not suggest any relationship with treatment or outcomes obtained but it is possible that specific antibody detection could be a helpful guide to more intensive immunotherapies in some cases. What this paper adds: 39% of children with brainstem encephalitis had antibodies to central nervous system surface antibodies. Antibody‐positive patients had phenotypes broadly associated with the specific antibody. Results did not suggest any relationship with immunotherapies or outcomes. Nevertheless, detection of antibodies at onset could be a guide to intensive immunotherapies. This article is commented on by Ramberger and Reindl on pages791–792 of this issue.